The Latvian Women’s Relief Corps during the Latvian War of Independence, 1919–1920 - Aiga Bērziņa-Kite (Acta Historica Universitatis Klaipedensis)
Significant changes in the social position of women in Europe, including Latvia, began in the 19th century, and peaked during the First World War. In Latvia, however, the momentum intensified during the War of Independence following the Great War, as women became increasingly involved in political, social and even military activities. They not only joined medical services and took on administrative roles, but also actively supported the Latvian army through their work with the Latvian Women’s Relief Corps (LWRC). Established in September 1919, the LWRC quickly became the most prominent and the largest women’s organisation in Latvia, earning recognition as the country’s first mass women’s association. This article discusses the founding and the activities of the LWRC during the Latvian War of Independence, including its contributions to supply, catering, sanitation, soldiers’ entertainment, social work, and more.